Melonhead - Kelly, Katy (Delacorte Press, 2009)
In the Washington, D.C. neighborhood of Capitol Hill, Lucy Rose's friend Adam "Melonhead" Melon, a budding inventor with a knack for getting into trouble, enters a science contest that challenges students to recycle an older invention into a new invention.